2023
DOI: 10.3389/fvets.2022.1086180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine viral diarrhea virus in cattle between 2010 and 2021: A global systematic review and meta-analysis

Abstract: BackgroundBovine viral diarrhea is one of the diseases that cause huge economic losses in animal husbandry. Many countries or regions have successively introduced eradication plans, but BVDV still has a high prevalence in the world. This meta-analysis aims to investigate the prevalence and risk factors of BVDV in the world in recent 10 years, and is expected to provide some reference and theoretical basis for BVDV control plans in different regions.MethodRelevant articles published from 2010 to 2021 were mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 129 publications
1
4
0
1
Order By: Relevance
“…We observed heterogeneity in the prevalence across studies, largely attributable to the variability in the detection methods and risk factors. Our results were consistent with previous reviews and meta-analyses on prevalence of BVDV that reported considerable variations [ 18 , 19 , 76 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed heterogeneity in the prevalence across studies, largely attributable to the variability in the detection methods and risk factors. Our results were consistent with previous reviews and meta-analyses on prevalence of BVDV that reported considerable variations [ 18 , 19 , 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…The estimated prevalence range of BVDV varies across different geographic regions and cattle populations [ 18 , 19 ]. It is unclear how much of this variation is a product of differences in detection methods, risk factors, or related covariates.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that the seroprevalence of BVD varies depending on the geographic region and the management practices of the cattle ( 34 ). The prevalence of BVD can range from < 2% to 97% in cattle herds ( 35 ). A seroprevalence of 26% and 35% was previously reported in Saudi Arabia ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine viral diarrhea (BVD) stands as the most significant and widespread infectious endemic disease affecting the global cattle population, causing substantial economic losses (Cowley et al 2014). BVD exhibits a high prevalence, persistent nature, and consequential clinical impact, making it a paramount infectious disease within the livestock industry (Su et al 2023). BVDV, a member of the Pestivirus genus within the Flaviviridae family, is characterized as a single-stranded, positive-sense RNA virus, alongside border disease virus (BDV) and classical swine fever virus (CSFV) (Ridpath 2003).…”
Section: Introductionmentioning
confidence: 99%